Being Womanish: A Womanist Perspective on Black Girlhood - King, Kishundra D. (Journal of pastoral theology, 2024)
This article asserts the value of Black girls’ lived experiences as a source for theological reflection in Womanist pastoral theology. In doing so, it proposes a methodological shift in Womanist pastoral theology and introduces a method called the Kaleidoscopic Analysis Perspective or KAP—a methodology designed with and for Black girls toward a Womanish vision of pastoral theology and care.